Analisis Kausalitas Pertumbuhan Ekonomi terhadap Penyerapan Tenaga Kerja Provinsi Sumatera Barat Tahun 2001-2020 - Nia Larasati; Yuni Prihadi Utomo (Universitas Batanghari Jambi, 2023)
Economic growth is defined as an effort to increase production with the aim of increasing output, which is usually measured by Gross Domestic Product (GDP) or using Gross Regional Domestic Product (GRDP). Absorption of labor is the number of jobs seen from the number of people working. This study aims to examine the causal relationship between economic growth and employment in West Sumatra Province in 2001-2020. The analytical tool used is the Granger causality test. The results of the Granger causality test for the variable Economic growth have a one-way causality relationship with employment. Whereas in West Sumatra Province, economic growth affects employment, but labor does not affect economic growth.